Elucidation Of Mercury Ion Binding Property Of A New Aryl Amide Type Podand By Electrochemical And Fluorescence Measurements - Guney, Sevgi; Yapar, Goenuel; Guney, Orhan; Yildiz, Guelcemal (Aperta, 2009)
A new aryl amide type podand (AAP), 1,8-bis(o-amidophenoxy)-3,6-dioxaoctane, was synthesized and its mercury ion binding property was elucidated by electrochemical and fluorescence measurements. The effects of supporting electrolyte, pH and scan rate on the electroreduction of AAP and on cyclic voltommogram of mercury ion were investigated by cyclic voltammetry (CV) and differential pulse voltammetry (DPV). It was observed that the complex formation between AAP and mercury ion exhibited pH-dependent behavior in different electrolyte solutions. Elucidation of such properties makes the AAP intriguing candidates as a modifying agent in sensor application for determination of mercury ion in mixture of aqueous solution.